Revolutionizing Business Operations: A Bibliometric Analysis of Enterprise Systems and Organizational Efficiency - Nanny Mayasari; Eva Andriani; Anas Romzy Hibrida (Eastasouth Institute, 2023)
This research paper presents a comprehensive bibliometric analysis focused on the intersection of enterprise systems and organizational efficiency, with the aim of understanding their role in revolutionizing business operations. The study examines the scholarly landscape surrounding Enterprise Resource Planning (ERP), Customer Relationship Management (CRM), and Supply Chain Management (SCM) systems. Through a meticulous exploration of peer-reviewed articles, the analysis identifies key trends, influential authors, significant themes, and research gaps within the domain. By synthesizing and analyzing a vast body of literature, this study offers insights into the evolution of enterprise systems, their implications for organizational efficiency, and directions for future research.